Karakteristik Fisik dan Antikapang Edible Film Whey Protein dengan Bubuk Rempah Sebagai Pembungkus Kopi - Syahrizal Nasution; Finna Fathin Fadilla; Anjelin Novita Sari; Lasuardi Permana (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Whey protein–based edible films represent an environmentally friendly alternative to conventional plastic packaging. The incorporation of natural bioactive compounds may further enhance their functional properties, including antimicrobial activity. This study aimed to evaluate the effects of ginger (Zingiber officinale) and cinnamon (Cinnamomum sp.) powder at different concentrations on the physical characteristics and antifungal activity of whey protein–based edible films intended for coffee powder packaging. Two types of edible films were prepared using the casting method: films containing ginger powder and films containing cinnamon powder, each formulated at concentrations of 0, 1, 2, and 3% (w/w). The films were evaluated for thickness, biodegradability, tensile strength, elongation, brewing time of ground coffee, and antifungal activity against Aspergillus niger. The results showed that ginger powder did not significantly affect film thickness, biodegradability, or elongation (p>0.05), but significantly influenced brewing time, tensile strength, and antifungal activity (p<0.05). The film containing 3% ginger exhibited the fastest brewing time (3.16 s), the lowest tensile strength (0.35 MPa), and the largest inhibition zone against A. niger (18.42 mm). Cinnamon powder significantly affected thickness, brewing time, tensile strength, and antifungal activity, but not biodegradability or elongation. The 3% cinnamon formulation produced the largest inhibition zone (18.67 mm), while the 1% formulation showed the highest tensile strength (0.93 MPa). Overall, the incorporation of ginger and cinnamon powders enhanced the antifungal functionality of whey protein–based edible films, indicating their potential as sustainable packaging materials for coffee powder.